PENGARUH PENDEKATAN CONTEXTUAL TEACHING AND LEARNING TERHADAP KETERAMPILAN MENULIS SURAT DI SEKOLAH DASAR - Veronika Mery; Siti Halidjah; K.Y Margiati (Universitas Tanjungpura, 2019)
AbstractThis study aimed to analyze whether there was influence of approach of Contextual Teaching and Learningto writing letter skill of V class elementary school 03 Pontianak City.. The method used was experimental method, while the research used pre-experimental design with one-group pretest-posttest design. Population and sample in this research was all student of class of V Primary School of State 03Pontianak Kota of amounted to 34 student. Data collection techniques used in this study were the technique of measurement techniques. The research instrument used was writing letter skill test. Based on result of data analysis from mean value pre-test 63,411 and average post-test 80,235. T test result obtained = 5%, with db = 33 was2,035.Because (15,378)> (2,035), so alternative hypothesis (Ha) accepted, it can be concluded that there was influence of applying Contextual Teaching and Learningto writing letter skill of V class elementary school 03 Pontianak City.Keywords:Learning Approach Contextual Teaching and Learning,Writing Letter Skill